2023
DOI: 10.1088/2399-6528/acdd4f
|View full text |Cite
|
Sign up to set email alerts
|

Observation of partial and infinite-temperature thermalization induced by repeated measurements on a quantum hardware

Abstract: On a quantum superconducting processor we observe partial and infinite-temperature thermalization induced by a sequence of repeated quantum projective measurements, interspersed by a unitary (Hamiltonian) evolution. Specifically, on a qubit and two-qubit systems, we test the state convergence of a monitored quantum system in the limit of a large number of quantum measurements, depending on the non-commutativity of the Hamiltonian and the measurement observable. When the Hamiltonian and observable do not commut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Recent results have attempted to study this phenomenology in simplified toy models [37,38]. However, in the case of noninteracting systems (e.g., free fermions), it has been shown that the transition has a radically different nature: the volume-law phase is immediately unstable for arbitrarily weak quantum measurements [39][40][41][42][43][44][45], and yet, in some cases, a subvolume phase can survive before the onset of the area-law phase [46][47][48][49][50], with a universality class more akin to problems of Anderson localization and disordered conductors, studied in the context of nonlinear sigma models [51,52]. In the interacting case, one of the main difficulties in studying individual trajectories of monitored systems lies in the fact that the probability of each trajectory depends on the state itself, in accordance with Born's rule.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results have attempted to study this phenomenology in simplified toy models [37,38]. However, in the case of noninteracting systems (e.g., free fermions), it has been shown that the transition has a radically different nature: the volume-law phase is immediately unstable for arbitrarily weak quantum measurements [39][40][41][42][43][44][45], and yet, in some cases, a subvolume phase can survive before the onset of the area-law phase [46][47][48][49][50], with a universality class more akin to problems of Anderson localization and disordered conductors, studied in the context of nonlinear sigma models [51,52]. In the interacting case, one of the main difficulties in studying individual trajectories of monitored systems lies in the fact that the probability of each trajectory depends on the state itself, in accordance with Born's rule.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been established that quantum systems subjected to both measurements and unitary dynamics offer another class of dynamical behavior described in terms of quantum trajectories [6], and well explored in the context of quantum circuits [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], quantum spin systems [26][27][28][29][30][31][32][33][34][35][36][37], trapped atoms [38], and trapped ions [39][40][41]. In this context, the bipartite entanglement entropy of isolated systems grows over time and eventually reaches the order of the system size as predicted by the celebrated Cardy-Calabrese quasi-particle picture [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%